Ptolemy's Optics, double-vision, and the technological afterimage. (August 2022) - Webster, Colin
Abstract: In contrast to earlier theorists within the Greek optical tradition, who relied almost exclusively on geometrical diagrams to articulate and explain vision, Ptolemy employed several material instruments in his investigation of sight. These included rulers, glass cylinders, mirrors, and a bronze plaque designed to measure angles of incidence and reflection. These devices allowed Ptolemy to expand the operational definition of vision far beyond that of his predecessors, as he explicated several previously unexamined visual behaviors, including binocular vision, diplopia, and refraction. This article argues that these tools did more than make new phenomena visible; they also set the parameters for what these phenomena looked like— sometimes to such a degree that features of these instruments merged with the visual behaviors that they rendered visible. In some cases, this occurred as a type of "double-exposure, " where the investigative tool became layered over top of the process of sight, such as when Ptolemy's "ruler" for investigating binocular vision became a template for imagining the mechanism of spatial perception employed by the eyes. In other cases, this merging occurred as a type of "technological afterimage, " where the instrument provided an implicit model for phenomena it was not directly investigating. Ptolemy's bronze plaque stands as an example of this second type, insofar as it inspired his account of ocular geometry and facilitated novel assertions about the eye's operations, even though it did not directly inspect these features. In general, this article thus outlines how the technologies of investigation can structure patterns of thought and naturalize certain physical arguments, whether for the phenomena that they directly articulate or for those indirectly associated with their particular use cases.